The inhibitory properties of the boiling extracts from Malus sylvestris and Syringa vulgaris flowers on the corrosion of stainless steel in sulphuric acid medium - Oo, Zaw Ye Maw; Nikolaychuk, Pavel Anatolyevich (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2024)
The inhibitory properties of the Malus sylvestris flower and Syringa vulgaris flower boiling extracts against the stainless steel EN Fe37-3FN corrosion in 0.5 M sulphuric acid medium were studied using electrochemical methods, including open circuit potential measurement, potentiodynamic polarisation and EIS. The addition of 10 mg/l of the Malus sylvestris flower extract slows the corrosion by 15%, and that of of 10 g/l – by 65%, while the addition of 10 mg/l of the Syringa vulgaris flower extract slows the corrosion by 30%, and that of of 1 g/l and more – by 65%. The Langmuir absorption model describes the adsorption of the components of the extracts on a surface of the steel, and the adsorption is physical in its nature. The Malus sylvestris flower and Syringa vulgaris flower extracts reveal themselves as interesting and environmentally safe substances for the steel corrosion rate reduction in acidic environments.